Low-frequency electroacupuncture and physical exercise decrease high muscle sympathetic nerve activity in polycystic ovary syndrome. - Stener-Victorin, E; Jedel, E; Janson, P; Sverrisdottir, Y (2009)
We have recently shown that polycystic ovary syndrome (PCOS) is associated with high muscle sympathetic nerve activity (MSNA). Animal studies support the concept that low-frequency electroacupuncture (EA) and physical exercise, via stimulation of ergoreceptors and somatic afferents in the muscles, may modulate the activity of the sympathetic nervous system. The aim of the present study was to investigate the effect of these interventions on sympathetic nerve activity in women with PCOS. In a randomized controlled trial, 20 women with PCOS were randomly allocated to one of three groups: low-frequency EA (n = 9), physical exercise (n = 5), or untreated control (n = 6) during 16 wk. Direct recordings of multiunit efferent postganglionic MSNA in a muscle fascicle of the peroneal nerve before and following 16 wk of treatment. Biometric, hemodynamic, endocrine, and metabolic parameters were measured. Low-frequency EA (P = 0.036) and physical exercise (P = 0.030) decreased MSNA burst frequency compared with the untreated control group. The low-frequency EA group reduced sagittal diameter (P = 0.001), while the physical exercise group reduced body weight (P = 0.004) and body mass index (P = 0.004) compared with the untreated control group. Sagittal diameter was related to MSNA burst frequency (Rs = 0.58, P < 0.005) in the EA group. No correlation was found for body mass index and MSNA in the exercise group. There were no differences between the groups in hemodynamic, endocrine, and metabolic variables. For the first time we demonstrate that low-frequency EA and physical exercise lowers high sympathetic nerve activity in women with PCOS. Thus, treatment with low-frequency EA or physical exercise with the aim to reduce MSNA may be of importance for women with PCOS.